The Attitudes of Arabic language teachers for the upper basic stage towards learning bridges activities in Almafraq Governorate - Al-Mashqabah, Ayoub Khalaf (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the attitudes of Arabic language teachers of the upper basic stage towards learning bridges activities from their point of view in Mafraq Governorate in Jordan. To achieve the objectives of the study, the descriptive survey method was used. The study used an electronic questionnaire consisting of (20) items, It was distributed amongst the study sample members, which consisted of (172) male and female teachers, and they were chosen by the available intentional sample method. The results of the study showed that the degree of the Arabic language teachers’ attitudes of the upper basic stage towards the activities of learning bridges from their point of view was high; with an arithmetic mean (2.40), and the absence of statistically significant differences at the level (α = 0.05) in the estimates of the study sample members due to the variables (gender, educational qualification, training courses), and in light of the results of the study, the researcher presented a group among the recommendations the most important is encouraging and educating teachers in Jordanian schools to benefit from the activities of learning bridges in teaching.